KOMPETENSI PROFESIONAL DOSEN PRODI PENDIDIKAN JASMANI KESEHATAN DAN REKREASI FAKULTAS KEGURUAN DAN ILMU KEPENDIDIKAN UNIVERSITAS MAHADEWA INDONESIA - Ni Wayan Ary Rusitayanti (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
Lecturer professional competence can be defined as the ability both knowledge, attitudes and skills that must be possessed by a lecturer to carry out and be accountable for his duties according to predetermined instructions. The aim of this research was to describe the lecturers’ professionalism at Prodi Pendidikan Jasmani Kesehatan dan Rekreasi FKIP Universitas Mahadewa Indonesia in academic year 2019/2020. This is a descriptive research with a survey method, which was carried out by distributing questionnaires. They were 233 students spreading from semester even from seven classes as the samples of the study, wich determined purposively based on the classes taught by the lecturers concerned. The finding proves that (1) the lecturers’ professionalism of Prodi Pendidikan Jasmani Kesehatan dan Rekreasi was assessed good by the students (mean: 4,95), (2) from the four competencies, personality competency reached the highest score (mean: 4,23), followed by Pedagogikal competency (mean: 4,15), professional competency (mean: 3.73). and finally social competency (mean: 3.73), and (3) all competence with both categories but there was some criticism from students who need attention